The Contribution of Google Classroom Application and Motivation to The Learning Outcomes of Web Programming - Guswara, Ade Mukhfir; Purwanto, Wawan (Journal of Education Technology, 2020)
Online learning is one of the most effective lessons that can be used during the Covid 19 pandemic. Online learning can be done with google classroom. The application of this method is still experiencing pros and cons. For this reason, the research objective was formulated to examine how much the contribution of the Google Classroom application and learning motivation of web programming learning outcomes. This research is descriptive correlational. The population in the study were 64 students. The sampling technique used simple random sampling, obtained 39 students as sample. Data collection using questionnaires and documentation. Questionnaire to collect data on Google Classroom application and learning motivation. Documentation to retrieve learning outcome data. The prerequisite analysis test was tested for normality, linearity, and multicollinearity. The data analysis method used simple regression and multiple regression. The study results are: (1) There is a positive and significant contribution of the Google Classroom application to learning outcomes (29.60%). (2) There is a positive and significant contribution of learning motivation to learning outcomes (20.30%). (3) A positive and significant contribution to the implementation of Google Classroom and learning motivation to learning outcomes was 49.90%.